PENGARUH PENGETAHUAN, KETERAMPILAN, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA MANDOR SADAP DI PT PERKEBUNAN NUSANTARA VII (PERSERO) - Mazdayani Mazdayani; Wuryaningsih Dwi Sayekti; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The research aims to determine the performance of the foreman and the influence of the knowledge, skills, motivation and compensation to performance of the foreman. The method used was census method and use primary and secondary data. The primary data obtained from questionnaires that has been analyzed their validity and reliability to the respondents through direct interviews and secondary data obtained from the literature and related agencies. Data collection was conducted from August to September 2013. The data was analyzed descriptively and verificatively with double linier regression and the data has been analyzed their Successive Interval Method. The results showed that (1) performance of the foreman tapping has the best, (2) knowledge, skills, motivation, and compensation influenced to performance of foreman tapping simultansly while knowledge, skills, and motivation influenced to performance of foreman tapping in PT Perkebunan Nusantara VII, Kedaton Unit Business and Way Berulu Unit Business partially. Keywords : compensation, knowledge, motivation, performance, skills